Decolonizing Islamic Education: Ibn Khaldun’s ‘Ilm al-‘Umran as a Critical Alternative to Eurocentric Educational Paradigms - Husni, Husni (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2025)
This article examines Ibn Khaldun’s ‘Ilm al-‘Umran as a critical framework for decolonizing Islamic education and challenging the dominance of Eurocentric educational paradigms. While modern educational systems in many Muslim and Global South contexts remain shaped by Western epistemological assumptions, standardized rationalities, and secular models of knowledge, Ibn Khaldun’s civilizational thought offers an alternative grounded in Islamic metaphysics, historical consciousness, empirical observation, social cohesion, and ethical formation. Using a qualitative library-based method and conceptual-critical analysis, this article explores the philosophical foundations of ‘Ilm al-‘Umran, its relevance to contemporary Islamic education, and its potential contribution to curriculum reform, critical consciousness, and epistemic justice. The discussion argues that ‘Ilm al-‘Umran should not be treated merely as a historical theory of civilization, but as a dynamic epistemological framework capable of reconstructing Islamic education in more contextual, ethical, and socially responsive ways. The article concludes that a Khaldunian approach can enrich decolonial education by integrating Islamic epistemology, local knowledge traditions, critical pedagogy, and civilizational awareness.